Pengaruh Media Sosial, Pembelian Impulsif, Dan Literasi Keuangan Syariah Terhadap Keputusan Penggunaan Shopee Paylater Pada Mahasiswa Muslim Jurusan Akuntansi di Politeknik Negeri Medan - Zalfa Sasqia Amanda; Supaino; Nurlinda; Diena Fadhilah; Rahmadani (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
This research looks at how social media, impulse buying, and knowledge about Islamic finance affect the choice to use Shopee PayLater among Muslim students studying Accounting at Medan State Polytechnic. The study used a quantitative approach with 100 participants chosen on purpose. Information was collected using a Likert scale survey and then analyzed with tests to check for validity and reliability, along with classical assumption tests for normality, heteroscedasticity, and multicollinearity. The findings revealed that individually, social media, impulse buying, and Islamic financial knowledge each had a positive and significant impact on the choice to use Shopee PayLater. Together, these three factors also showed a significant effect. This means that how much students engage with digital media, their tendency to buy things on impulse, and their understanding of Islamic finance play important roles in their decisions about using PayLater services.